Analytical Performance and Quality Indicators of Fully Automated Immunoassays for sFlt-1 and PlGF. (25th February 2022) - Higgins, Victoria; Ma, Liyan; Ragosnig, Bonny Lem; Melamed, Nir; Hladunewich, Michelle; James, Tim; Leite, Joao; Rozmanc, Mary; Barrett, Jon; Zaltz, Arthur; Yip, Paul M; Fu, Lei
Abstract: Background: The ratio of the antiangiogenic factor, soluble fms-like tyrosine kinase 1 (sFlt-1), to the proangiogenic factor, placental growth factor (PlGF), is associated with increased risk of preeclampsia. Here, we describe an analytical evaluation of the Elecsys sFlt-1 and PlGF assays at the first North American site in which they were clinically implemented. Methods: The analytical evaluation included short- and long-term imprecision, method comparison, accuracy, linearity, sample stability, limit of quantification verification, and measurement uncertainty. Quality indicators were also evaluated, including turnaround time and repeat test frequency. Results: Short-term (13-day) and long-term (12-month) imprecision for sFlt-1 and PlGF were <4% CV. Method comparison (n = 40) between Roche cobas e602 and e411 exhibited r > 0.99 and bias <10%. sFlt-1/PlGF ratio rule-out cutoffs (≤33 and ≤38) and rule-in cutoffs (>38, >85, and >110) exhibited negative percent agreement and positive percent agreement of 100%, respectively (n = 40). During the first 12 months, 257 orders were placed, repeat test frequency was 17.5%, mean time between repeat orders was 23 days, and 72.0% of results were reported within 2 h from sample receipt when quality control was run continuously. Conclusions: We describe analytical performance parameters and quality indicators of the Elecsys sFlt-1 and PlGF assays, which was the first North American clinical laboratory site to implement these assays in support of the institution's high-risk obstetrical unit.